2001
DOI: 10.1021/jp0020687
|View full text |Cite
|
Sign up to set email alerts
|

2D-Measurement of Penning Ionization Cross Section upon Molecular Orientation and Collision Energy in Ar(3P2,0) + CHCl3 Crossed Beam Reaction

Abstract: The Penning ionization cross section of Ar* + CHCl 3 crossed beam reaction is determined as the function of both molecular orientation and relative collision energy using oriented CHCl 3 molecular beam and TOF measurement. We find that the steric opacity function at low collision energies is well correlated to the exterior electron density distribution of the CHCl 3 molecular orbital that plays a key role in the electron exchange. At high collision energies, however, the reactivity along the molecular axis bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…1 As a benchmark model system for processes such as energy transfer and electron transfer, the reaction of metastable rare gas with small molecules has been widely studied. [7][8][9][10][11][12] Although the dependence on the magnetic substate M J has not been directly studied, it is expected that energy transfer processes depend markedly on the magnetic substate M J in the collision frame ͑reagent approach geometry͒. Actually, the importance of molecular orientation linked with the spatial distribution of molecular orbital has been directly studied in our laboratory by using an electric hexapole method for the reaction of metastable rare gas with small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…1 As a benchmark model system for processes such as energy transfer and electron transfer, the reaction of metastable rare gas with small molecules has been widely studied. [7][8][9][10][11][12] Although the dependence on the magnetic substate M J has not been directly studied, it is expected that energy transfer processes depend markedly on the magnetic substate M J in the collision frame ͑reagent approach geometry͒. Actually, the importance of molecular orientation linked with the spatial distribution of molecular orbital has been directly studied in our laboratory by using an electric hexapole method for the reaction of metastable rare gas with small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have used collision-energy-resolved techniques for Penning ionization reaction to investigate the anisotropic interaction around chlorine (Cl) atom with metastable atoms. Photoemission cross sections for CH radicals produced by collision of He*(2 3 S) atoms with CH 3 X (X = H, Cl, Br, and I) have been studied in the collision energy range of 120−210 meV, where the sum of these cross sections was correlated well with dipole-induced interaction of He*(2 3 S) with the targets, in particular, the approaches perpendicular to the C−Cl bond axis were found to be governed by an attractive interaction which shows that the simple correlation with the local dipole direction (C−Cl bond axis) does not always hold.…”
Section: Introductionmentioning
confidence: 99%
“…However, Albert et al suggested that the attractive interaction was located around an angle of 45° with respect to the C−Cl bond axis in the Ne*( 3 P 2,0 )−CH 3 Cl interaction system, which shows that the simple correlation with the local dipole direction (C−Cl bond axis) does not always hold. The reaction of Ar*( 3 P 2,0 ) with CHCl 3 was studied by Yamato et al using a combination of a TOF technique and an electric hexapole orientation technique, where the authors presented a correlation between collision energy and the steric effect . In our laboratory, attractive interaction potentials around the Cl atom have been studied for (CH 3 ) 3 CCl, chlorobenzene; trans -, cis -, and iso -dichloroethlenes; vinyl chloride; , and C 2 H 5 Cl, using the 2D-PIES technique.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well recognized that the alignment of the electron spin in the collision frame gives little effect on the dynamics as the Percival–Seaton hypothesis . Indeed, it has been reported that the atomic alignment effects on the most reaction processes are simply controlled by the configuration of the orbital angular momentum without spin effect ( L -dependence). However, the breakdown in the Percival–Seaton hypothesis (i.e., the importance of the spin-dependent interaction) infrequently has been reported. , We also experimentally observed the breakdown in the Percival–Seaton hypothesis ( J -dependence) in a few Ar ( 3 P 2 ) reactions. , Although it is not obvious that the Percival–Seaton hypothesis is of general relevance for the two-electron process on the triplet species involving two unpaired electron spins like Ar ( 3 P 2 , 4s [3/2] 2 ), in which the angular momentum of ion core (unpaired 3p orbital) weakly couples with the unpaired electron spin of 4s orbital, a negligible rank 4 moment (no spin alignment effect) has been observed in the most studies on the energy transfer reaction of oriented metastable rare-gas with small molecules. According to the Percival–Seaton hypothesis, the dynamics of Ar ( 3 P 2 ) reaction is dominantly controlled by the configuration of the half-filled Ar (3p) orbital of Ar ( 3 P 2 ) in the collision frame. In other words, the atomic alignment effect in the Ar ( 3 P 2 ) reaction can be represented by the moments up to rank 2 ( a 2 ), because the physics of the process is dominantly determined by the orbital angular momentum L (= 1) and its components M L ′ in the collision frame.…”
Section: Discussionmentioning
confidence: 64%
“…The reaction of metastable rare gas with small molecules has been widely studied as a benchmark system for the energy transfer process which is important as a fundamental process for chemical reactions such as initial steps in the photosynthetic process . The importance of molecular orientation linked with the spatial distribution of molecular orbital has been experimentally recognized in our laboratory. Recently, we developed an oriented Rg* ( 3 P 2 , M J = 2) beam and applied it to the energy transfer reactions. The significant atomic orbital alignment effects were recognized in the energy transfer reactions. Especially, we proposed that the alignment of the angular momentum of the ion core in the collision frame is conserved in the course of reaction process …”
Section: Introductionmentioning
confidence: 99%